Fabrico de papel em Braga no século XVI - Oliveira, Aurélio de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Through the present article, one publicises the production of paper in Braga (1530-1534), completely unknown until now, and thus leading this centre in Braga to become the second (or third) location in Portugal to witness the fabrication of paper.